The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/17455065221075913
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants and inequitable maternal and perinatal outcomes in Aotearoa New Zealand

Abstract: Objectives: Aotearoa New Zealand has demonstrable maternal and perinatal health inequity. We examined the relationships between adverse outcomes in a total population sample of births and a range of social determinant variables representing barriers to equity. Methods: Using the Statistics New Zealand Integrated Data Infrastructure suite of linked administrative data sets, adverse maternal and perinatal outcomes (mortality and severe morbidity) were linked to socio-economic and health variables for 97% of birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 61 publications
(92 reference statements)
0
19
0
1
Order By: Relevance
“…Disproportionate rates of hospitalisation could potentially be avoided with earlier primary care visits [16]. Māori and Asian mothers also have worse maternal and perinatal outcomes than NZ European/ European mothers, and lack of engagement with maternity care was one of the main determinants identified [17]. A systematic review also found that ethnic differences in pre-term birth can be explained by gaps in quality, continuity, and trust in maternity care providers [18].…”
Section: Introductionmentioning
confidence: 99%
“…Disproportionate rates of hospitalisation could potentially be avoided with earlier primary care visits [16]. Māori and Asian mothers also have worse maternal and perinatal outcomes than NZ European/ European mothers, and lack of engagement with maternity care was one of the main determinants identified [17]. A systematic review also found that ethnic differences in pre-term birth can be explained by gaps in quality, continuity, and trust in maternity care providers [18].…”
Section: Introductionmentioning
confidence: 99%
“…Participants considered actions such as food vouchers, living wages, universal income, and tax-free fruit and vegetables. Integrating upstream initiatives into a maternal health promotion strategy holds promise, with interventions such as food subsidy programmes ( McFadden et al , 2014 ) being a first step towards acknowledging this shortcoming, yet not enough to address the systemic and structural changes needed ( Dawson et al , 2022 ).…”
Section: Addressing Upstream Determinantsmentioning
confidence: 99%
“…30 Anne ölümlerinin engellenmesi ya da anne sağlığı sonuçlarının iyileştirilmesi için, öncelikli olarak sağlık sonuçlarında yaşanan eşitsizliklerin ve sağlık hakkaniyetsizliklerinin ele alınması ve sağlık sonuçları üzerinde etkisi olduğu gösterilen temel belirleyicilerin bu sürece dahil edilmesi gerektiği vurgulanmaktadır. 31…”
Section: Anne Sağliği Sonuçlarina Etki̇ Eden Sosyal Beli̇rleyi̇ci̇lerunclassified